uzasadnij ze m^3/kg* s^2=Nm^2/kg^2 daje naj
P = N m^2 / ( kg^2) = [ (kg *m/s^2 )*m^2]/kg^2 = [ kg*m^3 ]/ [ s^2 * kg^2] =
= m^3/ ( kg* s^2 ) = L
N = kg*m/s²
N*m²/kg²=kg*m/s²*m²/kg²=m/s²*m²/kg=m³/kg*s²
Pozdrawiam.
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
P = N m^2 / ( kg^2) = [ (kg *m/s^2 )*m^2]/kg^2 = [ kg*m^3 ]/ [ s^2 * kg^2] =
= m^3/ ( kg* s^2 ) = L
N = kg*m/s²
N*m²/kg²=kg*m/s²*m²/kg²=m/s²*m²/kg=m³/kg*s²
Pozdrawiam.